Transient heat stress protects from severe endothelial damage and dysfunction during prolonged experimental ex-vivo lung perfusion - Parapanov, Roumen; Debonneville, Anne; Allouche, Manon; Lugrin, Jérôme; Rodriguez-Caro, Helena; Liaudet, Lucas; Krueger, Thorsten (Frontiers in Immunology, 2024)
Introduction. The pulmonary endothelium is the primary target of lung ischemia-reperfusion injury leading to primary graft dysfunction after lung transplantation. We hypothesized that treating damaged rat lungs by a transient heat stress during ex-vivo lung perfusion (EVLP) to elicit a pulmonary heat shock response could protect the endothelium from severe reperfusion injury. Methods. Rat lungs damaged by 1h warm ischemia were reperfused on an EVLP platform for up to 6h at a constant temperature (T°) of 37°C (EVLP37°C group), or following a transient heat stress (HS) at 41.5°C from 1 to 1.5h of EVLP (EVLPHS group). A group of lungs exposed to 1h EVLP only (preheating conditions) was added as control (Baseline group). In a first protocol, we measured lung heat sock protein expression (HSP70, HSP27 and Hsc70) at selected time-points (n=5/group at each time). In a second protocol, we determined (n=5/group) lung weight gain (edema), pulmonary compliance, oxygenation capacity, pulmonary artery pressure (PAP) and vascular resistance (PVR), the expression of PECAM-1 (CD31) and phosphorylation status of Src-kinase and VE-cadherin in lung tissue, as well as the release in perfusate of cytokines (TNF, IL-1) and endothelial biomarkers (sPECAM, von Willebrand Factor -vWF-, sE-selectin and sICAM-1). Histological and immunofluorescent studies assessed perivascular edema and formation of 3-nitrotyrosine (a marker of peroxinitrite) in CD31 lung endothelium. Results. HS induced an early (3h) and persisting expression of HSP70 and HSP27, without influencing Hsc70. Lungs from the EVLP37°C group developed massive edema, low compliance and oxygenation, elevated PAP and PVR, substantial release of TNF, IL-1, s-PECAM, vWF, Eselectin and s-ICAM, as well as significant Src-kinase activation, VE-cadherin phosphorylation, endothelial 3-NT formation and reduced CD31 expression. In marked contrast, all these alterations were either abrogated or significantly attenuated by HS treatment.The therapeutic application of a transient heat stress during EVLP of damaged rat lungs reduces endothelial permeability, attenuates pulmonary vasoconstriction, prevents src-kinase activation and VE-cadherin phosphorylation, while reducing endothelial peroxinitrite generation and the release of cytokines and endothelial biomarkers. Collectively, these data demonstrate that therapeutic heat stress may represent a promising strategy to protect the lung endothelium from severe reperfusion injury.